(untitled) - FREEMAN, M. HERBERT; HANNA, J. MARSHALL \ KAHN, GILBERT (USA, 1968)
1.Processing cash receipts / 2.Processing cash payments / 3.Processing purchases of merchandise / 4.Processing sales on credit / 5.Adjusting and closing the books
Incluye indice analitico pag.295
Keywords: CONTABILIDAD